Methods of improving quality of grass-fed beef - Melvin C. Hunt; Donald H. Kropf; V. Chen; A. Harrison; O. Corte; C. Kuntapanit; M.E. Smith; J. Thomas; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1976)
Ten steers of known background, approximately 18 months old, and wintered on alfalfa and protein were finished on a brome and bluestem grazing program. Carcass characteristics were measured. The influence of conditioning carcass halves at 55 F until eight hours post-mortem was compared with conventional chilling at 36 F. Finally, the effects of vacuum storage and display on beef quality were evaluated.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Quality; Grass-fed beef; Carcass characteristics